Decentralized control mechanism underlying interlimb coordination of millipedes. (4th April 2017) - Kano, Takeshi; Sakai, Kazuhiko; Yasui, Kotaro; Owaki, Dai; Ishiguro, Akio
Abstract: Legged animals exhibit adaptive and resilient locomotion through interlimb coordination. The long-term goal of this study is to clarify the relationship between the number of legs and the inherent decentralized control mechanism for interlimb coordination. As a preliminary step, the study focuses on millipedes as they represent the species with the greatest number of legs among various animal species. A decentralized control mechanism involving local force feedback was proposed based on the qualitative findings of behavioural experiments in which responses to the removal of part of the terrain and leg amputation were observed. The proposed mechanism was implemented in a developed millipede-like robot to demonstrate that the robot can adapt to the removal of the part of the terrain and leg amputation in a manner similar to that in behavioural experiments.